The Coptic Version of The New Testament in The Northern Dialect Otherwise Called Sahidic and Thebaic with Interoduction, Critical Apparatus, and Literal English Translation: Volume I: The Gospel of S. Matthew and S. Mark - George William Horner 1849-1930 (UK The Clarendon Press, 1898)
Edited from Ms. Huntington 17 in The Bodleian Library
from VIII to CXLVIII . facsims.
Coptic and English on opposite pages . Register of Fragments and Estimate of The Version
Keywords: Holy Bible Texts and Translations (3fUhU hJQLeGJ GdcJGH GdebOSs; Bible